REINVENTING SOSOK MURABBI: MENJAGA KEDALAMAN SPIRITUAL PENDIDIK DI TENGAH DOMINASI KECERDASAN BUATAN (AI) - Surawardi; Nayla Azizah; Nazmah Rizka Amalia; Sayyidatunnisa; Shierin Nabila; Siti Fatimatuzzahra (ADDABANA: Jurnal Pendidikan Agama Islam, 2026)
This study discusses the reinventing of the murabbi figure as an effort to maintain the spiritual depth of educators amidst the dominance of artificial intelligence (AI). The rapid development of technology has brought significant changes to the field of education. On one hand, AI provides convenience in the learning process, but on the other hand, it also raises various challenges, particularly related to the weakening of spiritual values, ethics, and emotional closeness in education. This research employs a literature review method by analyzing various relevant sources, such as books, journals, and previous research findings. The results of the study indicate that the role of the murabbi cannot be replaced by technology, as the murabbi holds a primary function in nurturing the spiritual, moral, and character aspects of learners. Therefore, efforts to reinvent the role of the murabbi are necessary in order to remain relevant to the development of the times without losing the essence of Islamic education. The strategies that can be implemented include the purification of intention, the internalization of worship values in educational activities, the strengthening of ukhuwah, and the actualization of noble character in daily life.